Ethnomathematics exploration of fish trader activities in the traditional market of Punggulan Village, Asahan Regency - Angraini, Rini; Rakhmawati, Fibri (Indonesian Journal of Science and Mathematics Education, 2023)
Ethnomathematics connects mathematical concepts with cultural practices, providing insights into real-life applications. However, its integration into formal education remains limited. This study aims to explore the mathematical aspects of fish traders' activities in traditional markets and highlight their connection to cultural practices. A qualitative ethnographic approach was employed, utilizing library research, observations, and interviews for data collection. Data analysis followed the Miles and Huberman model, which involved data reduction, presentation, and conclusion. The findings reveal that fish trading activities encompass three main processes: measurement, packaging, and transactions. These activities incorporate mathematical concepts such as measurement, set theory, algebraic equations, weight comparison, social arithmetic, relations and functions, geometry, and probability. This study concludes that ethnomathematics serves as a bridge between mathematical theories and real-world applications. The implications of this research emphasize the importance of integrating ethnomathematics into formal education to provide students with contextual and meaningful learning experiences.